Economical -geographic problems of the development of the Karaganda agglomeration (Journal of Geography and Environmental Management, 2016)
This article considers the problem of the spatial organization of Central-Kazakhstan region. The results shows in the conditions of our country is brought to the forefront the task of a comprehensive and harmonious development of the Karaganda agglomeration, and elaboration of effective transformation of the socio-economic space of the region.
Keywords: territorial organization; spatial development; agglomeration